Body foods for life feel good, look good, stay good - Clarke, Jane (Weidenfeld & Nicolson, 1998)
This book shows that having a healthy body can be achieved by making basic changes to eating habits. Clarke's programme shows how to design a healthy eating style and how to use food to treat various common conditions and ailments, with advice on organic food, labelling, snacks for children, business lunches and how to prepare fresh, natural food.